Media and Print Culture Consumption in Nineteenth-Century Britain The Victorian Reading Experience - Rooney, Paul Raphael; Gasperini, Anna.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book explores Victorian readers' consumption of a wide array of reading matter. Established scholars and emerging researchers examine nineteenth-century audience encounters with print culture material such as periodicals, books in series, cheap serials, and broadside ballads. Two key strands of enquiry run through the volume. First, these studies of historical readership during the Victorian period look to recover the motivations or desired returns that underpinned these audiences' engagement with this reading matter. Second, contributors investigate how nineteenth-century reading and consumption of print was framed and/or shaped by contemporaneous engagement with content disseminated in other media like advertising, the stage, exhibitions, and oral culture. .
Introduction; Paul Raphael Rooney and Anna Gasperini -- 1. "Reader-Help: How to Read Samuel Smiles's Self-Help"; Barbara Leckie -- 2. "More than a 'book for boys'? Sir Thomas Malory's Le Morte Darthur and the Victorian Girl Reader"; Katie Garner -- 3. "'The Manuscript Magazines of the Wellpark Free Church Young Men's Literary Society"; Lauren Weiss -- 4. "Black Victorians and Anti-Caste: Mapping the Geographies of 'Missing' Readers"; Caroline Bressey -- 5. "John Dicks' Cheap Reprints Series, 1850s-1890s: Reading Advertisements"; Anne Humpherys -- 6. "Serialization and Story-Telling Illustrations: R. L. Stevenson Window-Shopping for Penny Dreadfuls"; Marie Léger-St-Jean -- 7. "Sensation and Song: Street Ballad Consumption in Nineteenth-Century England"; Isabel Corfe -- 8. "Reading Reynolds: The Mysteries of London as 'microscopic survey'"; Ruth Doherty -- 9. Cross-media Cultural Consumption and Oscillating Reader Experiences of Late-Victorian Dramatizations of the Novel: The Case of Fergus Hume's Madame Midas (1888)"; Paul Raphael Rooney -- 10. "Reading Theatre Writing: T.H. Lacy and the Sensation Drama"; Kate Mattacks -- Notes -- Bibliography -- Index.-.
Keywords: Books-History.; Civilization-History.; Printing and Publishing